Análise do comportamento estratégico de internacionalização das Born Globals e o papel das parcerias - Dourado, André Luís Figueiredo Santana (2017)
The present exploratory study had as its main goal to analyze the strategic behavior of Born Globals towards internationalization and the role of partnerships in that process. The specific objectives include characterizing the Born Globals founders’ profile, identifying the factors that lead the companies to globalize, identifying the reasons of choosing to enter certain countries, verifying how the internationalization strategic behavior of Born Globals had been modified through the years, as well as verifying the role that partnerships represented to Born Globals. Three organizations from Brazil and Italy from various sectors were analyzed. Interviews were carried out with the organizations’ stakeholders through a semi-structured questionnaire guide previously elaborated. All the interviews were recorded and then transcribed and submitted to content analysis. The study helped clarify some topics related to the role played by partnerships and the founders’ profile, more specifically, the temporal aspect of partnerships and the necessary entrepreneur profile of founders. Considering the strategic aspect, few significant changes were detected through the years, for the fact that both the planning and the behavior of the organizations did not change much as the process of internationalization advanced. Finally, the study has also found that some concepts in the literature of Born Globals are not in agreement with the results from the sample analyzed.